The first record of Ceratotarsonemus (Acari: Tarsonemidae) from the Oriental region with description of a new species from West Bengal, India - Kayal, Sandipan; Mondal, Priyankar; Karmakar, Krishna (Zootaxa, 2022)
A new tarsonemid species Ceratotarsonemus bengalicus Karmakar and Kayal sp. nov. is described from specimens collected on leaves of the mandarin orange, Citrus reticulata (Rutaceae), in Rishikhola, Kalimpong district, West Bengal, India. This is the first record of the genus Ceratotarsonemus De Leon, 1956 in the Eurasian mainland. An updated key to the species of Ceratotarsonemus is provided.